PENGARUH KESADARAN PERPAJAKAN, PELAYANAN FISKUS, SANKSI PERPAJAKAN, SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (STUDI EMPIRIS WAJIB PAJAK ORANG PRIBADI YANG TERDAFTAR PADA KANTOR PELAYANAN PAJAK PRATAMA BANDA ACEH TAHUN 2012-2015) - Nanda Rizki; Muhammad Saleh (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The number of tax payers is increase for years. But, it is not balanced with the level of tax compliance. The compliance problem becomes an obstacle in optimizing the  tax revenue. This study examines the level of compliance of individual taxpayers conducting business and professional services in Banda Aceh by using several independent variables such as awareness of the taxpayer, the service tax authorities, tax penalties and tax socialization. The purpose of this study was to analyze the influence of awareness of the taxpayer, the service tax authorities, tax penalties and tax socialization against and individual tax payer compliance conducting business and professional services. The population of this study is individual taxpayers conducting business and professional services in Banda Aceh. Based on data from the KPP Pratama Banda Aceh, until the end 2015 there were 155.799 individual tax payer conducting business and free job retention. Not all population have been used in this study to the time  and cost efficiency. Therefore, carried out the sampling. Sampling was done by simple random sampling method. The number of sample is 100 people. Primary data collection method used is a surveey method using questionnaires media. Data analysis techniques used in this study is the technique of multiple regression analysis. Based on the result of the analysis undertaken concluded the awareness of the tax payer, the service tax authorities, tax penalties and tax socialization have a positive and significant impact on taxpayer compliance.